Metode Dakwah KH. Ahmad Baha’uddin Nursalim (Gus Baha) Melalui Channel Santri Gayeng Di Media Youtube - Muhammad Qori Qordofa; Muhamad As'ad (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2022)
In a digital age where everyone USES social media to learn information and communicate remotely, new media is growing and becoming a human need for everyday life. Youtube is one of the new media that is so frequently visited by people with such needs and at any time that we can enjoy. The gayeng santri channel active on youtube that upshot the lecture of gus baha who is the lead actor. Gus Baha is very popular among the people his lectures are easy to accept and understandable with such a humourless attitude. We can enjoy gus baha's lectures at any time and anywhere with youtube makes it easier for us to gain knowledge of Islam.